Hepatectomy, RFA, and Other Liver Directed Therapies for Treatment of Breast Cancer Liver Metastasis: A Systematic Review - Rivera, Kevin; Jeyarajah, Dhiresh Rohan; Washington, Kimberly (Frontiers in Oncology, 2021)
Background The liver is the second most common site of breast cancer metastasis. Liver directed therapies including hepatic resection, radiofrequency ablation (RFA), transarterial chemo- and radio-embolization (TACE/TARE), and hepatic arterial infusion (HAI) have been scarcely researched for breast cancer liver metastasis (BCLM). The purpose of this review is to present the known body of literature on therapies for BCLM. Methods A systematic review was performed with pre-specified search terms using PubMed, MEDLINE, EMBASE, and Cochrane Review resulting in 9,957 results. After review of abstracts and application of exclusion criteria, 51 studies were included in this review. Results Hepatic resection afforded the longest median overall survival (mOS) and 5-year survival (45 mo, 41%) across 23 studies. RFA was presented in 6 studies with pooled mOS and 5-year survival of 38 mo and 11-33%. Disease burden and tumor size was lower amongst hepatic resection and RFA patients. TACE was presented in 8 studies with pooled mOS and 1-year survival of 19.6 mo and 32-88.8%. TARE was presented in 10 studies with pooled mOS and 1-year survival of 11.5 mo and 34.5-86%. TACE and TARE populations were selected for chemo-resistant, unresectable disease. Hepatic arterial infusion was presented in 5 studies with pooled mOS of 11.3 months. Conclusion Although further studies are necessary to delineate appropriate usage of liver directed therapies in BCLM, small studies suggest hepatic resection and RFA, in well selected patients, can result in prolonged survival. Longitudinal studies with larger cohorts are warranted to further investigate the effectiveness of each modality.